(untitled) (Advances in Applied Mathematics and Mechanics, 2018)
The two-winged insect hovering flight is investigated numerically using the lattice Boltzmann method (LBM). A virtual model of two elliptic foils with flapping motion is used to study the aerodynamic performance of the insect hovering flight with and without the effect of ground surface. Systematic studies have been carried out by changing some parameters of the wing kinematics, including the stroke amplitude, attack angle, and the Reynolds number for the insect hovering flight without ground effect, as well as the distance between the flapping foils and the ground surface when the ground effect is considered. The influence of the wing kinematic parameters and the effect of the ground surface on the unsteady forces and vortical structures are analyzed. The unsteady forces acting on the flapping foils are verified to be closely associated with the time evolution of the vortex structures, foil translational and rotational accelerations, and interaction between the flapping foils and the existed vortical flow. Typical unsteady mechanisms of lift production are identified by examining the vortical structures around the flapping foils. The results obtained in this study provide some physical insight into the understanding of the aerodynamics and flow structures for the insect hovering flight.